Preparation of Carboxymethyl Cellulose-g- Poly(acrylamide)/Attapulgite Porous Monolith With an Eco-Friendly Pickering-MIPE Template for Ce(III) and Gd(III) Adsorption - Wang, Feng; Zhu, Yongfeng; Wang, Aiqin (Frontiers in Chemistry, 2020)
Due to their high specific surface and metal-binding functional groups in their crosslinked polymeric networks, monolithic materials incorporating a porous structure have been considered one of the most efficient kinds of adsorbents for rare earth element recovery. Herein, a facile and novel monolithic multi-porous carboxymethyl cellulose-g-poly(acrylamide)/attapulgite was synthesized by free radical polymerization via green vegetable oil-in-water Pickering medium internal phase emulsion (O/W Pickering-MIPEs), which was synergically stabilized by attapulgite and tween-20. The homogenizer rotation speed and time were investigated to form stable Pickering-MIPEs. The effects of different types of oil phase on the formation of Pickering-MIPEs were investigated with stability tests and rheological characterization. The structure and composition of the porous material when prepared with eight kinds of vegetable oil were characterized by FTIR and SEM. The results indicate that the obtained materials, which have abundant interconnected porosity, are comparable to those fabricated with Pickering-HIPE templates. The adsorption experiment demonstrated that the prepared materials have a fast capture rate and high adsorption capacities for Ce(III) and Gd(III), respectively. The saturation adsorption capacities for Ce(III) and Gd(III) are 205.48 and 216.73 mg/g, respectively, which can be reached within 30 min. Moreover, the monolithic materials exhibit excellent regeneration ability and reusability. This work provides a feasible and eco-friendly pathway for the construction of a multi-porous adsorbent for adsorption and separation applications.